"Like a Dance": Performing Good Care for Persons with Dementia Living in Institutions. (30th September 2014) - Helleberg, Kristin Mjelde; Hauge, Solveig
Abstract : Dementia care is demanding, and health care workers can become emotionally exhausted and frustrated. Particularly, demanding aspects of dementia care include patient agitation and care-resistant behaviour. The aim of this study is to describe skilled staff's understanding of high-quality praxis in dementia care units in nursing homes. Eight nurses and care workers were individually interviewed, and a qualitative design was used. Participants were recruited from two nursing homes in two towns in eastern Norway. The data were analysed following the hermeneutic tradition inspired by Kvale. The analyses revealed three main findings describing good care: (a) to find: to identify the patient's personal characteristics, state, and needs, (b) to follow: to choose the right time and the tempo and to adapt to the patient's sensitivity, and (c) to lead: to be in the forefront and prepared and to change the patient's state. An overall interpretation of the findings is described by the metaphor of a dance between the patient and the caregiver.